Ecotourism development strategies of Lusi Island in Kedungpandan-Jabon Sidoarjo using SWOT Analysis - Kumala, Yufinca Mellyafara Indra; Laily, Aline Nurina Izzatul; Febrianty, Shelly Dwi; Falach, Muhammad Fajrul; Qoyum, Muhammad (Journal of Marine Resources and Coastal Management, 2023)
Lusi Island is a nature-based ecotourism site located in Sidoarjo, with its own uniqueness compared to the surrounding islands because it began as a dumping ground for Lapindo mud sediment. Lusi Island is providing several facilities to be used in protection, education, and recreation activities. The purpose of this study is to determine the development strategy of the Lusi Island tourist attraction by analyzing the existence of potential using the strength, weakness, opportunity, and threat (SWOT) analysis method at the ecotourism location. The results showed that the ecotourism development strategy of Lusi Island can be achieved by establishing cooperation between managers and various parties, controlling the impact of tourist attraction development, and adding adequate facilities and infrastructure to support better ecotourism.